Some provincial variations in Irish agriculture - Byrne, James J. (Statistical and Social Inquiry Society of Ireland, 1959)
The statistics relating to Irish agriculture as a whole convey an impression of general stability during the quarter century preceding 1950, but there the stability seems to end. Since then output has increased significantly and in addition the National Farm Survey 1955-1957 has shown that the regional returns accruing from similarly-sized enterprises and similar activities differ greatly. This prompts a curiosity about the nature of the pre-1950 stability?whether it applied equally to the component areas of agriculture or concealed development in some that was balanced and cancelled by a decay in others?and similarly with regard to the progress since 1950, whether it has been general and uniform or confined to particular regions.
Read before the Society, February 6 1959
Keywords: Provincial variations in agriculture; Regional agriculture; Agricultural output variations; 314.15